Determination of Efficacy of Metalaxyl Seed Treatment Fungicide on Incidence of Sorghum Diseases and Its Cost-Benefit in Borno State of Nigeria - B. I. , Richard; G. O. S, Ojo; T. Y, Maina (Asian Journal of Agriculture and Rural Development, 2014)
Sorghum (Sorghum bicolor (L.) Moench) is an economically valued food and cash crop in of Nigeria. In 2001 and 2002 cropping seasons, field experiments were conducted in a split-pot using randomized complete block design to determine the efficacy of Metalaxyl fungicide and it cost-benefit on incidence of sorghum diseases in Borno State at the Teaching and Research Farm of the Department of crop protection, University of Maiduguri. Six sorghum genotypes which include BES, ICSV 111, ICSV 400, Warwarbashi, Paul-Biya and Ex-Mali were used. The seeds were treated with 2.5g a.i/kg of Metalaxyi, plus control before sowing. Results showed that plants grown from the untreated seeds significantly had the highest mean anthracnose incidence of 33.6% and 33.9%, sooty stripe mean incidence of 42.1% and 38.6% in 2001 and 2002, and a higher covered smut mean incidence of 10.7% in 2002 respectively. Long smut incidence and grain yield were not significant among treated and untreated seeds in 2001 and 2002. Treated plants had an increased yield of 0.28% and 28.9% more than the untreated in 2001 and 2002 respectively. Treated Ex-Mali and untreated Paul-Biya, Ex-Mali recorded higher cost-benefit ratio and net profit in monetary valued. The physiological attributes of each sorghum genotypes can dictate their choice for local uses as well.